If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3n + 3) = 9(6n + 5) * 8 Reorder the terms: 3(3 + 3n) = 9(6n + 5) * 8 (3 * 3 + 3n * 3) = 9(6n + 5) * 8 (9 + 9n) = 9(6n + 5) * 8 Reorder the terms: 9 + 9n = 9(5 + 6n) * 8 Reorder the terms for easier multiplication: 9 + 9n = 9 * 8(5 + 6n) Multiply 9 * 8 9 + 9n = 72(5 + 6n) 9 + 9n = (5 * 72 + 6n * 72) 9 + 9n = (360 + 432n) Solving 9 + 9n = 360 + 432n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-432n' to each side of the equation. 9 + 9n + -432n = 360 + 432n + -432n Combine like terms: 9n + -432n = -423n 9 + -423n = 360 + 432n + -432n Combine like terms: 432n + -432n = 0 9 + -423n = 360 + 0 9 + -423n = 360 Add '-9' to each side of the equation. 9 + -9 + -423n = 360 + -9 Combine like terms: 9 + -9 = 0 0 + -423n = 360 + -9 -423n = 360 + -9 Combine like terms: 360 + -9 = 351 -423n = 351 Divide each side by '-423'. n = -0.829787234 Simplifying n = -0.829787234
| 6(x-5)=-48 | | 0.5x-0.3(2-x)=4.6 | | -4=a+6 | | 9x^2+3x-3xy-y=0 | | 5x^2-2x^2+9x^2+x^2=0 | | .01x+.10x+.25(35-2x)=4.07 | | 5+3x+2x+7=2 | | 4p^3+36p=0 | | 42-x=19 | | c-4=13.7 | | 6x*x+7x-20=0 | | n-6=-10 | | 0=x^2-25x+144 | | 9(5+x)=15(10+x) | | 4x-(9-3x)=18x-1 | | w=4+8 | | 15-j+5j+2=-14 | | p=4+8 | | -4(x+4)=5-(-4) | | 2(-18)+3=3(-18)+7 | | -5(x+7)=5-(-1) | | 4x=3(49-x) | | 5+h=-6 | | .67x=5 | | 17.50+4p=53.50 | | 7-5m=45 | | 2(5x+2)=8x | | -4(3x+1)+x=3x+10 | | .5*.5*.5*.5= | | 10-4x=28 | | 98x=-1 | | x^2-19x+9=0 |